What Justice Entails - Muñiz-Fraticelli, Víctor (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2012)
In The Birthright Lottery, Ayelet Shachar subjects the institution of birthright citizenship to close scrutiny by applying to citizenship the historical and philosophical critique of hereditary ownership built up over four centuries of liberal and democratic theory, and proposing compelling alternatives drawn from the theory of private law to the usual modes of conveyance of membership. Nonetheless, there are some difficulties with this critique. First, the analogy between entailed property and birthright citizenship is not as illustrative as Shachar intends it to be; second, the mechanism of the birthright privilege levy is insufficient for addressing structural impediments to growth; and third, the principle of ius nexi, while an important corrective to currently dominant principles of nationality, will likely have effects both unnecessary and insufficient to correct the injustices that Shachar identifies. In the end, the most significant improvements in the lives of the neediest persons on the planet are more likely advanced through conventional arguments for the lowering of barriers to the circulation of goods, labor, and capital. This shift in attention from opening borders to extending citizenship risks being a distraction from more effective means of addressing the injustices associated with global inequality.